Modern facades of Post and Telegraph Agencies - Vieira, Carlos Eduardo; Benincasa, Vladimir; Bortolucci, Maria Angela P. C. S. (National Journal of City Management, 2024)
Until not too long ago, postal and telegraph services were the means of communication that connected people throughout the Brazilian territory. Initially, both services were provided by separate entities and operated in distinct buildings, often in rented, loaned, and precarious spaces. The construction of proprietary buildings began from the 1st Republic (1889) onwards, following the eclectic style, the prevalent architectural style of the time. After 1930, with the unification of those two public services into a single department, the construction of proprietary buildings gained a new momentum. This study focuses on that new moment, providing examples of the new architecture of Post and Telegraph agencies, with standardized projects built throughout the country. Such structures featured "modern" facades following the rationalization of Art Deco for reflecting the new era in Brazil and the modern image desired by the federal government for the country. The study concentrates on iconographic analyses of agencies built before and after 1930 towards demonstrating the transition of an important period in Brazil, reflected in its Post and Telegraph agencies, but extending to all national public services.
Keywords: Post and telegraph; Architecture; Public service